Verification HPLC method of quantitative determination of amlodipine in tablets - Khanin, V; Komarytskyy, І; Bevz, N; Georgiyants, V (Annals of Mechnikov's Institute, 2020)
Introduction. Amlodipine ((±)-2-[(2- aminoetoksi)methyl]-4-(2-chlorophenyl)-1,4-dihydro-6- methyl-3,5-pyridine dicarboxylic acid 3-ethyl 5-methyl ester) as besylate and small tally belongs to the group of selective long-acting calcium channel blockers, dihydropyridine derivatives. In clinical practice, as antianginal and antihypertensive agent for the treatment of cardiovascular diseases. It is produced in powder form, substance and finished dosage forms (tablets of 2.5, 5 and 10 mg). The scientific literature describes methods of quantitative determination of the drug by spectrophotometry – by his own light absorption and by reaction product with aloksan, chromatography techniques, kinetic-spectrophotometric method in substances and preparations and methods chromatomass spectrometry and stripping voltammetry. For the quantitative determination of amlodipine besylate British Pharmacopoeia and European Pharmacopoeia recommend the use of liquid chromatography method. In connection with the establishment of the second edition of SPhU and when it is comprised of articles on the finished product, we set out to analyze the haracteristics of the validation of chromatographic quantitative determination of amlodipine besylate tablets and to verify the analytical procedure. Material & methods. In conducting research using substance amlodipine besylate series number AB0401013. Analysis subject pill “Amlodipine” series number 20113 manufacturer of “Pharmaceutical company “Zdorovye”. Analytical equipment used is: 2695 chromatograph with diode array detector 2996 firms Waters Corp. USA using column Nova-Pak C18 300 x 3,9 mm with a particle size of 4 μm, weight ER-182 company AND Japan, measuring vessel class A. Preparation of the test solution. To accurately sample powder tablets equivalent to 50 mg amlodipine, add 30 ml of methanol, shake for 30 minutes, dilute the solution to 50.0 ml with methanol and filtered. 5 ml of methanol solution adjusted to a volume of 100.0 ml. Preparation of the working standard solution sample amlodipine besylate. 50.0 mg of amlodipine RCC dissolved in methanol and dilute with the same solvent to 50.0 ml. 5.0 ml of this solution argue with methanol to volume 100.0 ml. Before the major controlled trials validated the existence of documents certifying the suitability vykorystovanoho equipment, raw materials and chemicals. Validation of the methodology was carried out in accordance with the requirements of SPhU. Results & discussion. Linearity methods defined within 80-120% of nominal concentrations. The linearity of the methods supported by the entire range of concentrations studied (b=0.9845, Sb=0,01473, a=1.5282, Sa=1.4956, S0=0.5486, r=0.9992). It is proved that the validated method characterized by sufficient convergence and accuracy over the entire range of concentrations (ΔZ=1.03, δ%=0.09). Conclusion. During verification methods of quantitative determination of amlodipine besylate tablets were studied characteristics validated HPLC method: accuracy, linearity, precision, specificity, and internal laboratory precision. Validation technique characteristics do not exceed the critical value of error (1.6%) and characterized by qualitative analytical indicators. This technique can be correctly reproduced in the laboratory conditions, and is independent of the excipients.